Concentrated Growth Factors (CGF) Induce Osteogenic Differentiation in Human Bone Marrow Stem Cells - Rochira, Alessio (Biology (Basel), 2020)
SIMPLE SUMMARY: Osteogenesis is a complex physiologic process that occurs during development as well as during damaged bone regeneration. This process requires several growth factors that act on stem cell populations, including Bone Marrow Stem Cells (BMSC). The present study fits into the research field for safe improvement of cell osteogenesis induction. In this context there is a great interest on an autologous and biocompatible blood derived product, named Concentrated Growth Factor (CGF). In particular, the ability of CGF to induce osteogenic differentiation of human BMSC (hBMSC) in vitro was here investigated. The osteogenic differentiation was evaluated measuring typical osteogenic markers such as alkaline phosphatase enzyme activity, matrix mineralization of hBMSC, and expression of some osteogenic-related genes. The results show that CGF alone is able to induce osteogenic differentiation of hBMSC. This finding opens up further, interesting perspectives in the biotechnological use of CGF in the tissue regeneration field. ABSTRACT: Bone regeneration is a complex process regulated by several factors that control overlapping biological processes, coordinating interactions among distinct cell populations. There is a great interest in identifying new strategies for inducing osteogenesis in a safe and efficient manner. Concentrated Growth Factor (CGF) is an autologous blood derived product obtained by centrifugation of venous blood following the procedure set on the Silfradent device. In this study the effects of CGF on osteogenic differentiation of human Bone Marrow Stem Cells (hBMSC) in vitro have been investigated; hBMSC were cultured with CGF or osteogenic medium, for 21 days. The osteogenic differentiation was evaluated measuring alkaline phosphatase (ALP) enzyme activity, matrix mineralization by alizarin red staining and through mRNA and protein quantification of osteogenic differentiation markers by Real-time PCR and Western blotting, respectively. The treatment with CGF stimulated ALP activity and promoted matrix mineralization compared to control and seems to be more effective than osteogenic medium. Also, hBMSC lost mesenchymal markers and showed other osteogenic features. Our study showed for the first time that CGF alone is able to induce osteogenic differentiation in hBMSC. The application of CGF on hBMSC osteoinduction might offer new clinical and biotechnological strategies in the tissue regeneration field.